Estudo da influência das crenças, conhecimentos e fontes de informação nas condutas dos cuidadores no manejo da febre na criança - Ana Carolina Micheletti Gomide (2011)
Introduction: the fever phobia of parents, concerns and inappropriate treatment of fever in children has been documented for approximately two decades. The understanding of parents regarding fever, can determine their concerns, fears and reaction to child care. Aim: verifying knowledge, beliefs, sources of information, practices and attitudes of parents and caregivers in the management of fever in children. Methodology: This is a descriptive cross-sectional of character qualitative and quantitative. Participants were recruited from september 2010 to january 2011. The study population consisted all parents and caregivers who sought the emergency department at Childrens Hospital John Paul II, with reports that the child has a fever or had a fever in the past 72 hours. The sample consisted of 286 participants. All answered a questionnaire about management of fever and 6 parents/caregivers were invited to participate in a semi-structure interview. The data collected were tabulated and submitted to univariate and bi-varied with the aid of software SPSS (Statistical Package for Social Science) version 15.0 and STATA version 10.0, in order to establish the statistical treatment to answer questions raised by research. Results/ Discussion: To detect fever, 202 (70,5%) use a thermometer and 84 (29,4%) use palpation of body parts or observe some signs such as irritation, skin-colored or prostration. The vast majority of participants considered dangerous fever 279 (97,6%) and only 80 (28%) believed that fever is benefical. Parents and caregivers reported that reported that fever can cause serious health problems in their children, in relation to damage than can cause fever, were cited on a larger scale convulsion 201 (70,3%), somnolence 51 (17,8%), weakness 45 (15,7%), dehydration 20 (7%) and brain damage 11 (3,8%). For fever control in 275 (96,2%) administered antipyretics and 40 (14%) use antibiotics, but the majority of respondents unaware of the adverse effects of these medications. For information about fever parents use vehicles such as the internet 49 (17%), books 24 (8%), TV 47 (16,4%) and newspapers 17 (5,9%) and also seek information to health professionals that 155 (54%), friends 24 (8%) and relatives 85 (29,7%). Conclusions: The fear exacerbated raises concerns related to their conceptions direct their conduct and practices of management of fever. Fever phobia persists, and parents and caregivers had feelings of insecurity to caring for a feverish child.